Sense of presence - Hiemstra, Auke-Florian (The Eriskay Connection, 2024)
Rogier Maaskant’s (NL) enchanting images unveil a diverse array of insects in flight during twilight and nighttime – in forests and above fields, ditches, and ponds around Rotterdam. By using strobe light, his single exposures provide a unique view of the flight of caddisflies, moths, lacewings, dragonflies, gnats, and various other species that illustrate the rich biodiversity. For Sense of Presence, Maaskant collaborated with scientists and butterfly experts. His work is in line with the current era of renewed interest in nature and a widespread awareness of the need to protect it
Edition: 1000
Keywords: Maaskant, Rogier -- 1971-; Insekten; Fluginsekten; Fotografie; Bildband